Malignant transformation arising in mature cystic teratoma (Journal of Pathology of Nepal, 2016)
Background: The prognosis of patients with malignant transformation arising within mature cystic teratoma is poor. However, preoperative diagnosis is dif cult due to its rarity. The aim of this study was to evaluate the clinical and histopathological characteristics of such malignancies. Materials and Methods: A retrospective cross sectional study on a series of cases was performed in the Department of Pathology, Patan Academy of Health Sciences, Patan Hospital, Lalitpur, Nepal from April 2011 to March 2016. Data from the histopathology database were analyzed using SPSS version 16.0. Results: Mature cystic teratoma comprised 230 cases (57.6%) out of total 399 cases of ovarian neoplasms. Malignant transformation was noted in 7 (3%) of the mature cystic teratoma. The mean age at diagnosis of patients with malignant transformation of mature cystic teratoma was 47.57 years. The size of the tumors ranged from 7-14cm. The mean diameter of tumor was 10.28cm. There was signi cant difference in age between mature cystic teratoma and malignant transformations arising within mature cystic teratoma. No signi cant association was noted in tumor size. Torsion was noted in a single case. Squamous cell carcinoma was the most common malignant tumor seen in 5 cases. The TNM stage distribution was T1aNx for 4 cases, T2aNx for one case and T3aNx for 2 cases. Conclusion: Squamous cell carcinoma is the most common malignancy arising in mature cystic teratoma. Advanced age is a signi cant risk factor for malignant transformation in mature cystic teratoma.